Point-of-Care Capillary Blood Creatinine: A Prospective study in Cardiology and Nephrology Outpatients - Vilaine, Eve; Gabarre, Paul; Beauchet, Alain; Seidowsky, Alexandre; Auzel, Olivier; Hauguel-Moreau, Marie; Dubourg, Olivier; Mansencal, Nicolas; Essig, Marie; Massy, Ziad A. (Cardiology and Cardiovascular Medicine, 2021)
Background: The radiological or interventional use of contrast medium exposes patients to a risk of contrast-induced nephropathy. Pre-existing kidney failure is a major risk factor. Point-of-Care Capillary blood creatinine tests are promising; their speed might help to optimize treatment decisions and patient care in these situations. Methods: The objective of the present study was to assess the ability of a new point of care capillary blood creatinine test (Stat Sensor X-press, Nova Biomedical Cooperation, Waltham, MA, USA) to diagnose kidney failure, relative to a standard lab-based plasma creatinine assay. A total of 113 patients 33 women (29.2%) were included. The capillary blood creatinine concentration was significantly correlated with the plasma creatinine concentration in both men (Pearson’s r [95% Confidence Interval (CI)] = 0.84 [0.75 – 0.89]; p<0.001) and women (Pearson’s r [95%CI] = 0.95 [0.89 – 0.97]; p<0.001). The test’s diagnostic performance was satisfactory, its sensitivity was 70% [35 – 93] in women and 78% [52 - 94] in men, and its specificity was 91% [72 - 99] in woman and 93% [84 - 98] in men. Conclusion: Rapid Point-of Care Capillary creatinine test is an easy-to-use, accurate tool for detecting kidney failure before a patient is exposed to procedures involving contrast medium. The POC test performed less well in patients over the age of 75 and in patients with high plasma creatinine level